Understanding the Gold-Inflation Nexus in Malaysia: Hedge and Safe Haven Perspectives - Mohd Fahmi Ghazali; Nurul Fasyah Mohd Ussdek; Hooi Hooi Lean; Ahmad Monir Abdullah; Anath Rau Krishnan (Universiti Malaysia Sarawak, 2022)
The main objective of this study is to examine the roles of gold as a hedge or a safe haven against inflation in Malaysia. We propose the standard and quantile techniques in the volatility models, with a time-varying conditional variance of regression residuals based on TGARCH specifications. We found that gold only plays a minor role as a hedge and safe haven against inflation since their returns do not evolve at the same pace as inflation. On the other hand, the rolling regression results reveal that shelter incidents against purchasing power loss only occasionally occur at different times and not consistently across holding periods. We conclude that gold does not have the ability to secure Malaysian investment during high inflationary periods and at all times. Thus, Malaysian investors should hold a well-diversified portfolio to earn sustainable returns and protection from purchasing power loss.